Results of the 2020 Performance Audit in the Cajeme City Council: Efficacy, Efficiency and Transparency in Municipal Public Management - Valle Luna, Pedro Benoni (Posgrados de la División de Ciencias Económica Administrativas, 2022)
Given the relevance of the Inspection in the municipal governments of the State of Sonora, and considering the recent Report of Results of the Public Account, issued by the Superior Institute of Audit and Inspection (ISAF, for its acronym in Spanish) regarding the Fiscal Year 2020 for the Cajeme City Counsil, arises the interest of analyzing the results of the Performance Audit of that Municipality, the main item, which led the aforementioned state auditing body to propose a rating of 66 in its Public Account, which shows in general terms, a non-effective performance, and a non-efficient exercise of Public Expenditure in relation to most of the goals set forth in the Budgetary Program for Fiscal Year 2020. In this research work, we will provide information about the results of the Performance Audit performed to the Cajeme City Counsil regarding its Budgetary Program for Fiscal Year 2020, determining how such results have an impact on the Cajeme community, addressing too the relevance of the attention to the legal obligations of Transparency in the effective and efficient conclusion of the programmatic goals, in order to offer recommendations from a professional and citizen point of view, that may be useful for the strengthening of the Municipal Public Management.